2022
DOI: 10.3390/molecules27249000
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemia Activity and Mechanism of Platinum(II)-Based Metal Complexes

Abstract: Transition metal complexes have continued to constitute an appealing class of medicinal compounds since the exceptional discovery of cisplatin in the late 1960s. Pt(II)-based complexes are endowed with a broad range of biological properties, which are mainly exerted by targeting DNA. In this study, we report a significant biological investigation into and computation analyses of four Pt(II)-complexes, namely, LDP-1–4, synthesized and characterized according to previously reported procedures. Molecular-modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In other studies, complexes have been identified which act as intercalating agents because they have the capacity to be introduced between nitrogenous bases of DNA. This intercalation mechanism has mainly been reported for complexes with planar ligands and aromatic systems [ 14 , 18 ]. Furthermore, complexes that interact with DNA through the major and minor grooves have also been reported [ 54 ].…”
Section: Recent Studies On Platinum(ii) and Copper(ii) Complexes And ...mentioning
confidence: 85%
See 1 more Smart Citation
“…In other studies, complexes have been identified which act as intercalating agents because they have the capacity to be introduced between nitrogenous bases of DNA. This intercalation mechanism has mainly been reported for complexes with planar ligands and aromatic systems [ 14 , 18 ]. Furthermore, complexes that interact with DNA through the major and minor grooves have also been reported [ 54 ].…”
Section: Recent Studies On Platinum(ii) and Copper(ii) Complexes And ...mentioning
confidence: 85%
“…Such characteristics include increased solubility, specificity, effectiveness and stability. Ligands such as phosphines [ 11 , 12 , 13 , 14 , 15 , 16 ], dithiocarbamates [ 17 , 18 ], triazoles [ 19 ], saccharinates [ 11 , 15 ], terpyridines [ 20 ], benzothiazoles [ 21 , 22 ], Schiff bases [ 23 ], benzimidazoles [ 24 ], imides [ 25 , 26 , 27 , 28 ] and others [ 10 , 29 ], as well as metal ions such as palladium, ruthenium, nickel, rhodium, iridium, gold and copper, have all been used in the development of new coordination compounds or metal complexes by researchers taking a biological approach [ 5 , 30 , 31 , 32 ]. At the same time, functionalization processes have also been developed for the controlled administration of drugs from existing complexes; these include liposome encapsulation [ 33 ], macrocycles, metal nanoparticles and carbo nanotubes [ 34 , 35 ], as well as bioconjugation [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, 20 μL of 0.01% resazurin (Promega) was added to each well. The fluorescence of resazurin was measured after 4 h of incubation using an Infinite M2000 Pro plate reader (Tecan) at an Ex/Em = 550 nm/590 nm wavelength . The viability of the cells was calculated in comparison to the DMSO control.…”
Section: Methodsmentioning
confidence: 99%
“…With this in mind, and given the polyanionic nature of DNA, the use of cationic compounds capable of sliding along the surface of the target once in immediate proximity, establishing a second type of interaction with it, could prove very important. Moreover, several Pt (II) intercalating compounds have been developed over the years, and their cytotoxicity against different tumor cell lines has been demonstrated 28–30 . Recently, several types of metal complexes have also shown promising results in antiviral and antimicrobial research 31–34 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several Pt (II) intercalating compounds have been developed over the years, and their cytotoxicity against different tumor cell lines has been demonstrated. [28][29][30] Recently, several types of metal complexes have also shown promising results in antiviral and antimicrobial research. [31][32][33][34] Herein, in this paper, we report the biological activity results of sixteen Pt (II) compounds, capable of intercalating between DNA nucleobases, evaluated against three cancerous cell lines, namely, MDA-MB 231 (breast adenocarcinoma), U87 (glioblastoma), and U2-OS (osteosarcoma), which have been selected as they are known to express DNA G-quadruplex (G-4) secondary structures.…”
Section: Introductionmentioning
confidence: 99%